Temozolomide is additive with cytotoxic effect of irradiation in canine glioma cell lines - Nina Simona Tresch (Wiley, 2021)
Abstract Background Similar to human glioblastoma patients, glial tumours in dogs have high treatment resistance and a guarded prognosis. In human medicine, the addition of temozolomide to radiotherapy leads to a favourable outcome in vivo as well as a higher antiproliferative effect on tumour cells in vitro. Objectives The aim of the study was to determine the radio‐ and temozolomide‐sensitivity of three canine glial tumour cell lines and to investigate a potential additive cytotoxic effect in combined treatment. Additionally, we wanted to detect the level of MGMT promoter methylation in these cell lines and to investigate a potential association between MGMT promoter methylation and treatment resistance. Methods Cells were treated with various concentrations of temozolomide and/or irradiated with 4 and 8 Gy. Radiosensitization by temozolomide was evaluated using proliferation assay and clonogenic assay, and MGMT DNA methylation was investigated using bisulfite next‐generation sequencing. Results In all tested canine cell lines, clonogenicity was inhibited significantly in combined treatment compared to radiation alone. All canine glial cell lines tested in this study were found to have high methylation levels of MGMT promoter. Conclusions Hence, an additive effect of combined treatment in MGMT negative canine glial tumour cell lines in vitro was detected. This motivates to further investigate the association between treatment resistance and MGMT, such as MGMT promoter methylation status.